3D-Printed Models of Cleft Lip and Palate for Surgical Training and Patient Education. (March 2018) - Chou, Pang-Yun; Hallac, Rami R.; Shih, Ellen; Trieu, Jenny; Penumatcha, Anjani; Das, Priyanka; Meyer, Clark A.; Seaward, James R.; Kane, Alex A.
Background: Sculpted physical models and castings of the anatomy of cleft lip and palate are used for parent, patient, and trainee education of cleft lip and palate conditions. In this study, we designed a suite of digital 3-dimensional (3D) models of cleft lip and palate anatomy with additive manufacturing techniques for patient education. Methods: CT scans of subjects with isolated cleft palate, unilateral and bilateral cleft lip and palate, and a control were obtained. Soft tissue and bony structures were segmented and reconstructed into digital 3D models. The oral soft tissues overlying the cleft palate were manually molded with silicone putty and scanned using CT to create digital 3D models. These were then combined with the original model to integrate with segmentable soft tissues. Bone and soft tissues were 3D printed in different materials to mimic the rigidity/softness of the relevant anatomy. These models were presented to the parents/patients at our craniofacial clinic. Visual analog scale (VAS) surveys were obtained pertaining to the particular use of the models, to ascertain their value in parental education. Results: A total of 30 parents of children with cleft conditions completed VAS evaluations. The models provided the parents with a better understanding of their child's condition with an overall evaluation score of 9.35 ± 0.5. Conclusions: We introduce a suite of 3D-printed models of cleft conditions that has a useful role in patient, parental, and allied health education with highly positive feedback.